2018
DOI: 10.2196/publichealth.9088
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the Development of a Mobile HIV Prevention Intervention for Men Who Have Sex With Men and Hijras in Mumbai: Qualitative Study

Abstract: BackgroundAs Internet and mobile phone use expands in India, there is an opportunity to develop mobile health (mHealth) interventions for marginalized populations, including men who have sex with men (MSM) and hijras (transgender women), hesitant to access traditional health care systems.ObjectiveThe purpose of this study was to determine if an mHealth intervention was acceptable to MSM and hijras living in Mumbai, and if so, what features would be useful in targeting the prevention of HIV acquisition and to i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Second, interactive interventions—those that allowed participants to engage directly with online content or other users—demonstrated greater impact on HIV testing uptake compared with the overall pooled estimate. Interactivity in digital interventions has been associated with achieving a greater impact on behavior change across a range of health areas [ 75 - 77 ] and has been identified as a desired feature of digital HIV prevention interventions among MSM and TW [ 43 , 78 ]. Third, our subanalysis also identified that interventions that used mainstream social media platforms, such as Facebook, were also associated with greater uptake of HIV testing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, interactive interventions—those that allowed participants to engage directly with online content or other users—demonstrated greater impact on HIV testing uptake compared with the overall pooled estimate. Interactivity in digital interventions has been associated with achieving a greater impact on behavior change across a range of health areas [ 75 - 77 ] and has been identified as a desired feature of digital HIV prevention interventions among MSM and TW [ 43 , 78 ]. Third, our subanalysis also identified that interventions that used mainstream social media platforms, such as Facebook, were also associated with greater uptake of HIV testing.…”
Section: Discussionmentioning
confidence: 99%
“…However, all interventions that utilized social media platforms were also categorized as interactive, making it difficult to isolate the source of the enhanced effect. Social networking–based interventions are commonly used for sexual health promotion [ 79 ], and the use of existing social media platforms has been identified as a way to enhance retention among young MSM and TW in online HIV prevention activities [ 43 ]. Using existing and well-utilized social media platforms may also enhance the reach of digital HIV prevention interventions [ 80 ] compared with those that are delivered through new or separate platforms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most men, including a substantial number of firsttime testers, claimed the app gave them a "nudge" to test for HIV. Other studies have shown the potential of a digital intervention to support early HIV diagnosis in men (Rawat et al, 2018;Wood et al, 2019;Zhao et al, 2018). However, individuals' autonomy to test for HIV was shaped by factors other than the app, suggesting that digital applications like EPIC-HIV1 may be most effective for men when used to support effective decentralised HIV care (Li et al, 2017;Liu et al, 2016;Nakanwagi et al, 2016;Nhassengo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%